Association of mitochondrial variants and haplogroups identified by whole exome sequencing with Alzheimer's disease. Issue 2 (20th June 2021) - Zhang, Xiaoling; Farrell, John J.; Tong, Tong; Hu, Junming; Zhu, Congcong; ,; Wang, Li‐San; Mayeux, Richard; Haines, Jonathan L.; Pericak‐Vance, Margaret A.; Schellenberg, Gerard D.; Lunetta, Kathryn L.; et al.
Abstract: Introduction: Findings regarding the association between mitochondrial DNA (mtDNA) variants and Alzheimer's disease (AD) are inconsistent. Methods: We developed a pipeline for accurate assembly and variant calling in mitochondrial genomes embedded within whole exome sequences (WES) from 10, 831 participants from the Alzheimer's Disease Sequencing Project (ADSP). Association of AD risk was evaluated with each mtDNA variant and variants located in 1158 nuclear genes related to mitochondrial function using the SCORE test. Gene‐based tests were performed using SKAT‐O. Results: Analysis of 4220 mtDNA variants revealed study‐wide significant association of AD with a rare MT‐ND4L variant (rs28709356 C>T; minor allele frequency = 0.002; P = 7.3 × 10 −5 ) as well as with MT‐ND4L in a gene‐based test ( P = 6.71 × 10 −5 ). Significant association was also observed with a MT‐related nuclear gene, TAMM41, in a gene‐based test ( P = 2.7 × 10 −5 ). The expression of TAMM41 was lower in AD cases than controls ( P = .00046) or mild cognitive impairment cases ( P = .03). Discussion: Significant findings in MT‐ND4L and TAMM41 provide evidence for a role of mitochondria in AD.